Situation and some Factors Related to Injury of Children Under 5 Years Old in 3 Communes of Hoai Duc District, Hanoi City in 2020 - Thi Kim Dung, Nguyen; Van Thang, Chu (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 38 No 2, 2022)
Research objective: describe the current situation and some factors related to injury accidents of children under 5 years old in 3 communes of Hoai Duc district, Hanoi city 2020. Objects and research methods: A cross-sectional descriptive study on 901 families with children under 5 years old in 3 communes of Hoai Duc district, Hanoi city in 2020. Research results: About the situation : The rate of accidents and injuries is 14.77%. Most of the injuries in 2-year-olds accounted for 40.53%. The leading causes are: Fall/fall (41.05%); sharp objects (14.74%) and burns (12.63%). The most common time for children to have accidents and injuries is from 6 am to 12 am (45.79%) and 12 to 18 pm (34.74%). Accidents and injuries are unintentionally caused by children themselves, accounting for 62.11%. 97.4% of children received first aid within 30 minutes of the accident. Regarding the relationship: Male caregivers are 1.46 times more likely to cause injury to children than female caregivers. Caregivers of children who have completed university/college/secondary education are 8.85 times less likely to cause their children to suffer from an accident than people who do not attend school (OR: 8.85, 95%CI: 1.92) – 40.88). Male children have 1.47 times higher risk of having a stroke than girls (OR: 1.47, 95% CI: 1.08 – 2.00), the relationship is statistically significant with p < 0.05. Conclusion: The rate of accidents and injuries is still quite high at 14.77%, most of the children have self-inflicted injuries at a time when there are few caregivers at home. Education level, caregiver's gender, and child's gender are related to the risk of injury.